Good Corporate Governance with Religiosity Approach in Realizing Accountability at Sharia Financial Institution - Aziz, Roikhan Mochamad; Salsabila, Fauziyah Latiefa (Universitas Siliwangi, 2023)
Introduction to The Problem: The issue of Good Corporate Governance (GCG) develops along with the occurrence of several types of conflicts that occur between groups of stakeholders. So the company encourages business people to present a good corporate management mechanism.Purpose/Objective Study: This research aims to build an efficient corporate governance system, effective management, disclosure in accurate financial reporting, as well as fair and transparent accounting records so as to create accountability to God, Man, and Nature.Design/Methodology/Approach: This study uses a descriptive writing method with a qualitative approach.Findings: The results of this study explain that the concept of Good Corporate Governance (GCG) with the Sharia Enterprise Theory and Hahslm Theory approaches will reflect transparency to achieve harmonious relations related to the interets of the company, people, nature, and Allah SWT.Paper Type: Research Article or General Review